THE DEFINITION OF THE COMMERCIAL ATTRACTION AREA AND THE SPATIAL ORGANIZATION OF THE WEEKLY USED CAR MARKET IN BIR OUNAS, AIN BEIDA MUNICIPALITY (ALGERIA) - Abbes Chemami,; Salah Bouchemal,; Aissa Boulkaibet, (International Journal of Innovative Technologies in Social Science, 2024)
To analyze and examine the factors influencing the determination of the trade attraction field of the Bir Ounas used car market in the Ain Beida Municipality, we conducted a field study based on statistical methods and quantitative criteria, through a descriptive analysis of the market and incoming vehicles. The study was supported by a survey aimed at market visitors, including questions about their geographical origin and reasons for choosing the market, with a cartographic representation of the results.In light of the field study results conducted during the first semester of 2024, it was confirmed that the market's geographical position, located at the center of several large urban agglomerations in northeastern Algeria and near the intersection of national roads, plays a significant role in influencing the commercial attractiveness index, despite the development and management issues it experiences The research revealed that over half of the visitors come from outside the Oum El Bouaghi province. The dense commercial territory extends to the east of the Oum El Bouaghi province (Khenchela, Tébessa, Souk Ahras), but becomes less concentrated and strong as it moves west towards provinces like Constantine, Batna, and Mila.